2020
DOI: 10.1177/2165079920911564
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Public Health Employee Engagement and Retention: One U.S. National Center’s Analysis and Approach

Abstract: Background: Employee engagement, exemplified by positive perceptions of supervisors, workplace, and job, improves productivity and employee retention. We identified the extent of and barriers to employee engagement at Centers for Disease Control and Prevention’s (CDC) National Center for HIV/AIDS, Viral Hepatitis, STD, and TB Prevention (NCHHSTP). Methods: In 2015, NCHHSTP’s leadership collected baseline data through a centerwide Employee Engagement Pulse Survey (EEPS) from NCHHSTP’s full-time Civil Service em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The focus on employee engagement was found to be one of the most important aspects of an effort to increase employee retention in an organization, as revealed in previous research. According to Kgomo &Swarts, (2010) andSmith et al, (2020), employee involvement had a positive impact on employee retention. Therefore, it can be concluded that one of the company's strategies to increase employee retention was by increasing employee engagement as a supportive factor.…”
Section: Discussionmentioning
confidence: 98%
“…The focus on employee engagement was found to be one of the most important aspects of an effort to increase employee retention in an organization, as revealed in previous research. According to Kgomo &Swarts, (2010) andSmith et al, (2020), employee involvement had a positive impact on employee retention. Therefore, it can be concluded that one of the company's strategies to increase employee retention was by increasing employee engagement as a supportive factor.…”
Section: Discussionmentioning
confidence: 98%